The coverage of maternal continuum-of-care and associated factors in the Lao People’s Democratic Republic: A population-based cross-sectional study - Sengdavy Xaypadith; Ai Aoki; Kimihiro Nishino; Eiko Yamamoto (PLoS ONE, 2026)
Maternal, newborn, and child health remains a global challenge, with continuum-of-care serving as a key strategy to improve health outcomes. This study aimed to examine the coverage of maternal continuum-of-care and to identify factors associated with continued care in the Lao People’s Democratic Republic (Lao PDR). This is a cross-sectional study including 2,612 women aged 15–49 years who participated in Lao Social Indicator Survey III, 2023, gave live birth in the two years preceding the interview, and responded to questions about antenatal care (ANC), postnatal care (PNC), and delivery assistance during their last pregnancy and childbirth. Maternal continuum-of-care was defined as having ≥ 4 ANC visits, delivery by a skilled birth attendant (SBA), and at least one PNC visit after discharge and within six weeks postpartum. In the selection process of the study participants, all women who had home delivery were excluded due to missing data on the three components of the continuum-of-care. Of the 2,612 women (with facility-based delivery), 83.1% received ≥ 4 ANC visits, 82.2% received both ≥ 4 ANC visits and SBA delivery, and 3.3% completed the maternal continuum-of-care. Factors associated with completion of the continuum-of-care included classifying as a high wealth index category (adjusted odds ratio [AOR] = 2.19, 95% confidence interval [CI]: 1.19–4.04), having the last child as male (AOR = 1.65, 95% CI: 1.04–2.61) and receiving a maternal health check before discharge from the health facility (AOR = 2.40, 95% CI: 1.06–5.41). Hmong-Mien women were significantly less likely to complete the continuum-of-care than Lao-Tai women (AOR = 0.24, 95% CI: 0.06–0.91). The completion of the maternal continuum-of-care in Lao PDR was very low. Strengthening maternal health checks before discharge, addressing gender norms and financial barriers, and promoting culturally sensitive, community-based, and family-engaged approaches may improve coverage.